Implementation Of The Project-Based Learning (PJBL) Model In The Dance And Drama Arts Education Course To Develop Student Creativity - Rachmawati, Putri (CV. Inara, 2024)
This study aims to apply the Project Based Learning (PjBL) learning model to dance and drama education in the Elementary School Teacher Education Study Program, FIPP-Yogyakarta State University through art performances in developing student creativity for one semester. Project Based Learning (PjBL) is a learning model that centers on students using projects or activities as a means of learning to gain learning experiences, achieve attitude, knowledge and skill competencies. This research is a type of qualitative research with a descriptive method approach. The researcher conducted a study of dance and drama learning through the performing arts process in developing student creativity in the dance and drama education course. The subjects of the study were all fourth semester students at Yogyakarta State University who took the dance and drama education course in the 2023/2024 Academic Year. The results of this study show that the creativity of dance and drama works in art performances is very good, able to show good creativity, able to apply the project-based learning model, good teamwork and creativity, more independent, able to create new things and productive in managing performing arts management in the dance and drama process. The implementation of the project-based learning model was declared successful and a success in the dance and drama arts education course.